The Kagiso-Shanduka trust educational innovation: an exploration of the initiation phase of the KST whole-school development model in the Free State province - Khasake, Mpho Given (My University, 2018)
This study explored the initiation phase of the Kagiso-Shanduka Trust (KST) whole-schooldevelopment model, which is implemented in Fezile Dabi (FD) education district in the Free State Province, South Africa. The research was conceptualised and conducted between 2015 and 2016. I employed a qualitative research methodology and case-study approach to collect data to answer my research questions. The data sources emerged from interviews conducted with five participants who I purposively selected. They are executive members from KST and a senior official from Fezile Dabi District in the Free State Department of Education. I interviewed each participant separately at their places of work. The study identifies the nature of processes and the factors that influenced the adoption of the KST W-SD model. I used the concepts of engagement and mobilisation to unpack the processes and the factors in the initiation phase of the KST W-SD model because they are key concepts that provides descriptive data. These data point out the direction and intensity the change is taking and determine the sustainability elements in the initiation of a change project. Engagement and mobilisation are conscious efforts that bring about insights on the totality of a change project and the adaptations instituted in the initiation phase of a change project. The following findings emerged from the study: 1) there are conditions that gave rise to the need for the model, 2)the model was conceptualised by each organisation individually (KT and FS), then in a dual partnership (KST) and in a tripartite (PPP) through stakeholder engagement and mobilisation, 3) the descriptions fits the conceptualisation, 4)stakeholder engagement and mobilisation created awareness, interest, problem solving opportunities and ownership during interactions of partners, 5) the model was consequently consolidated with six elements, 6) the model elements are integrated and provide a comprehensive package for whole school development, and 7) the model is a product of investment on organisational capacities and capabilities developed over a period of time as well as shared interest and purpose. It is recommended that more research involving private, public partnerships be conducted more frequently on current educational innovation models.
A dissertation submitted to the University of the Witwatersrand in fulfillment of the requirements for the degree of Master of Education Johannesburg, 2018
Keywords: Educational innovations--South Africa; School improvement programs; Educational planning--South Africa